IMPROVEMENT OF THE METHODOLOGY OF HYGIENIC ASSESSMENT OF THE CONDITIONS OF ORPHANAGES «MEHRIBONLIK» - Djalolidinova, Ashurova Manzura; Djalolidinova, Ashurova Manzura; Djalolidinova, Ashurova Muqaddas; Kobilovna, Ruzmatova Hiloloy (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the problem of hygienic assessment of educational and educational conditions, as well as the development of measures to improve the health status of pupils of the Mehribonlik houses. The following research tasks were identified and solved: Hygienic assessment of the placement, construction and equipment of orphanages “Mehribonlik”; living conditions of children living in the Mehribonlik houses; assessment of the microclimate and lighting conditions of the Mehribonlik houses; assessment of the health status of pupils living in the houses of "Mehribonlik"; price of the regime and nutritional conditions of pupils living in the Mehribonlik houses; Hygienic recommendations have been developed aimed at improving the living conditions of pupils living in the Mehribonlik houses.